 Proof.

9

A

2 A

:

X

u

Z

A

=

Y

u

Z

A

, 9

A

2 A

:

"

X

u

F

"

A

=

"

Y

u

F

"

A

) 9

A

2 A

:

"

X

u

F

"

A

u

F

A

=

"

Y

u

F

"

A

u

F

A , 9

A

2 A

:

"

X

u

F

A

=

"

Y

u

F

A , "

X

u

F

A

=

"

Y

u

F

A , "

X

"

Y

,

X

Y

.

On the other hand,

"

X

u

F

A

=

"

Y

u

F

A , f

X

u

Z

A

0

j

A

0

2 Ag

=

f

Y

u

Z

A

1

j

A

1

2 Ag ) 9

A

0

;

A

1

2 A

:

X

u

Z

A

0

=

Y

u

Z

A

1

) 9

A

0

; A

1

2 A

:

X

u

Z

A

0

u

Z

A

1

=

Y

u

Z

A

0

u

Z

A

1

) 9

A

2 A

:

X

u

Z

A

=

Y

u

Z

A

.

Proposition 4.163.

The relation

is a congruence

4.1

for each of the following:

1. a meet-semilattice

A

;

2. a distributive lattice

A

.

Proof.

Let

a

0

; a

1

; b

0

; b

1

2

A

and

a

0

a

1

and

b

0

b

1

.

1.

a

0

u

b

0

a

1

u

b

1

because

(

a

0

u

b

0

)

u A

=

a

0

u

(

b

0

u A

) =

a

0

u

(

b

1

u A

) =

b

1

u

(

a

0

u A

) =

b

1

u

(

a

1

u A

) = (

a

1

u

b

1

)

u A

.

2. Taking the above into account, we need to prove only

a

0

t

b

0

a

1

t

b

1

. We have

(

a

0

t

b

0

)

u A

= (

a

0

u A

)

t

(

b

0

u A

) = (

a

1

u A

)

t

(

b

1

u A

) = (

a

1

t

b

1

)

u A

:

Denition 4.164.

We will denote

A

/ (

) =

A

/ ((

)

\

A

A

)

for a set

A

and an equivalence

relation

on a set

B

A

. I will call

a congruence on

A

when

(

)

\

A

A

is a congruence on

A

.

Theorem 4.165.

Let

F

be the set of lters over a boolean lattice

Z

and

A 2

F

. Consider the

function

:

Z

(

D

A

)

!

Z

/

dened by the formula (for every

p

2

Z

(

D

A

)

)

p

=

f

X

2

Z

j "

X

u

F

A

=

p

g

:

Then:

1.

is a lattice isomorphism.

2.

8

Q

2

q

:

¡

1

q

=

"

Q

u

F

A

for every

q

2

Z

/

.

Proof.

8

p

2

Z

(

D

A

):

p

=

/

;

because of theorem

4.147

Thus it is easy to see that

p

2

Z

/

and

that

is an injection.

Let's prove that

is a lattice homomorphism:

(

p

0

u

F

p

1

) =

f

X

2

Z

j "

X

u

F

A

=

p

0

u

F

p

1

g

;

p

0

u

Z

/

p

1

=

f

X

0

2

Z

j "

X

0

u

F

A

=

p

0

g u

Z

/

f

X

1

2

Z

j "

X

1

u

F

A

=

p

1

g

=

f"

X

0

u

F

"

X

1

j

X

0

; X

1

2

Z

;

"

X

0

u

F

A

=

p

0

^ "

X

1

u

F

A

=

p

1

f

X

0

2

Z

j "

X

0

u

F

A

=

p

0

u

F

p

1

g

=

(

p

0

u

F

p

1

)

:

Because

p

0

u

Z

/

p

1

and

(

p

0

u

F

p

1

)

are equivalence classes, thus follows

p

0

u

Z

/

p

1

=

(

p

0

u

F

p

1

)

.

To nish the proof it is enough to show that

8

Q

2

q

:

q

=

(

"

Q

u

F

A

)

for every

q

2

Z

/

. (From

this it follows that

is surjective because

q

is not empty and thus

9

Q

2

q

:

q

=

(

"

Q

u

F

A

)

.) Really,

(

"

Q

u

F

A

) =

f

X

2

Z

j "

X

u

F

A

=

"

Q

u

F

Ag

= [

Q

] =

q:

This isomorphism is useful in both directions to reveal properties of both lattices

Z

(

D

A

)

and

Z

/

.

Corollary 4.166.

If

Z

is a boolean lattice then

Z

/

is a boolean lattice.

Proof.

Because

Z

(

D

A

)

is a boolean lattice (theorem

2.79

).

4.1

See Wikipedia for a denition of congruence.

4.3 Filters on a poset

75